An Analysis of Subtitling Strategies in Inside Out Movie Based on Gottlieb's Theory - Jajang Setiawan; Retno Setya Budiasningrum; Ali Satri Efendi; Suhardianto (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Movie subtitling is a critical aspect of audiovisual translation, bridging the gap between languages and cultures. This study aims to explore the strategies used in the subtitle translations of the the movie Inside Out and evaluate the accuracy level of the translations associated with the identified strategies. In this study, the research uses the script and subtitle of the movie Inside Out (2015) by utilizing the ten translation strategies in Gottlieb's theory to review the data found. The results show that the transfer strategy is the most applied strategy by the translator while translating this Inside Out (2015) movie.